With Power Comes Responsibility – A Rangelands Perspective on Forest Landscape Restoration - Vetter, Susanne (Frontiers in Sustainable Food Systems, 2020)
Tree planting has long been promoted to avert climate change and has received renewed impetus in recent years with the Bonn Challenge and related forest restoration initiatives guided by the forest and landscape restoration (FLR) framework. Much of the focus for reforestation and afforestation is on developing countries in Africa, Asia and South America, where large areas of rangelands in drylands and grassy biomes are portrayed as “degraded,” “unused,” and in need of more trees. This perception is rooted in persistent theories on forests and desertification that widely shaped colonial policy and practice and remain influential in today's science-policy frameworks. From a rangelands perspective, the global FLR thrust raises two main concerns. First, inappropriate understandings of the ecology of drylands and grassy biomes encourage afforestation, grazing restriction and fire suppression, with negative impacts on hydrology, carbon storage, biodiversity, livestock production and pastoral livelihoods. Second, their target-driven approach requires large-scale afforestation and massive funding to achieve. Nearly half of the area pledged to the Bonn Challenge is in fact destined for forestry and other commercial plantations, which threaten pastoral livelihoods and cause ecological damage while having very limited potential to mitigate climate change. As the officially endorsed framework of the Bonn Challenge and related global restoration initiatives, FLR has become a powerful instrument for guiding global restoration efforts and funding. Its proponents have a responsibility to ensure that the framework is evidence-based and underpinned by appropriate ecological models for different ecoregions.